Pathogenic Tconvs promote inflammatory macrophage polarization through GM‐CSF and exacerbate abdominal aortic aneurysm formation. Issue 3 (8th February 2022) - Li, Dan; Li, Jingyong; Liu, Henan; Zhai, Luna; Hu, Wangling; Xia, Ni; Tang, Tingting; Jiao, Jiao; Lv, Bingjie; Nie, Shaofang; Hu, Desheng; Liao, Yuhua; et al.
Abstract: Abdominal aortic aneurysms (AAAs) elicit massive inflammatory leukocyte recruitment to the aorta. CD4 + T cells, which include regulatory T cells (Tregs) and conventional T cells (Tconvs), are involved in the progression of AAA. Tregs have been reported to limit AAA formation. However, the function and phenotype of the Tconvs found in AAAs remain poorly understood. We characterized aortic Tconvs by bulk RNA sequencing and discovered that Tconvs in aortic aneurysm highly expressed Cxcr6 and Csf2. Herein, we determined that the CXCR6/CXCL16 signaling axis controlled the recruitment of Tconvs to aortic aneurysms. Deficiency of granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), encoded by Csf2, markedly inhibited AAA formation and led to a decrease of inflammatory monocytes, due to a reduction of CCL2 expression. Conversely, the exogenous administration of GM‐CSF exacerbated inflammatory monocyte infiltration by upregulating CCL2 expression, resulting in worsened AAA formation. Mechanistically, GM‐CSF upregulated the expression of interferon regulatory factor 5 to promote M1‐like macrophage differentiation in aortic aneurysms. Importantly, we also demonstrated that the GM‐CSF produced by Tconvs enhanced the polarization of M1‐like macrophages and exacerbated AAA formation. Our findings revealed that GM‐CSF, which was predominantly derived from Tconvs in aortic aneurysms, played a pathogenic role in the progression of AAAs and may represent a potential target for AAA treatment.